Claartje Rasterhoff, Painting and Publishing as Creative Industries: The Fabric of Creativity in the Dutch Republic, 1580-1800 - van Ginhoven, Sandra (BMGN - Low Countries Historical Review, 2017)
Claartje Rasterhoff, Painting and Publishing as Creative Industries: The Fabric of Creativity in the Dutch Republic, 1580-1800 (Amsterdam: Amsterdam University Press, 2017, 344 pp. isbn 9789089647023).